OBSERVATIONS ON SOME ASPECTS OF BIOLOGY OF THE BLACK CROAKER ATROBUCCA NIBE (JORDAN AND THOMPSON) FROM KAKINADA - Murty, V Sriramachandra (Indian Journal of Fisheries, 2011)
Observatioins on some aspects of biology of Atrobucca nibe are made fromKakinada. The length-weight relationship is described by the equation log W =-5.524308 + 3.213476 log L. The fluctuations in relative condition factor appearto be associated with fluctuations in gonad cycle. Individuals release ova in twobatches during the spawning season which extends from Feibuary to July in thearea. The length at fiirst maturity is estimated at 145 mm. The s-sx rstio indicatespredominance of males in most months and length groups.